TEACHER CREATIVITY EFFORTS IN PROVIDING LEARNING MEDIA AT STATE SENIOR HIGH SCHOOL 2 “YOUTH VOCATIONAL” IN ACEH TAMIANG - Tengku Muhammad Sahudra (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to determine the extent of the efforts made by teachers in preparing learning media in Aceh Tamiang State Senior High School 2 “Youth Vocational”. This research is a quantitative study that analyzes data using quantitative formulas. Data is taken from all teachers in the school and then mathematically analyzed which can be justified academically. The results of this study indicate that there is no influence of teacher creativity on media learning in State Senior High School 2 of Youth Vocational in Aceh Tamiang District. This can be seen from the reality that (1) With the selection of teaching media to help teachers to deliver subject matter and help students to better understand the lessons presented. (2) With the help of students to better understand the subject matter delivered, it will be more motivating student achievement. (3) From the calculation shows that the value of t (count) is 0.909 while the value of t (table) is 1.70 (for dk = n-2 = 4 and the significance level of 0.05) Keywords:     Teacher Creativity Efforts, Providing Learning Media, State SeniorHigh School 2 of Youth Vocational, Aceh Tamiang